Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fphy.2020.00379
|View full text |Cite
|
Sign up to set email alerts
|

A Guided Tour of ab initio Nuclear Many-Body Theory

Abstract: Over the last decade, new developments in Similarity Renormalization Group techniques and nuclear many-body methods have dramatically increased the capabilities of ab initio nuclear structure and reaction theory. Ground and excited-state properties can be computed up to the tin region, and from the proton to the presumptive neutron drip lines, providing unprecedented opportunities to confront two-plus three-nucleon interactions from chiral Effective Field Theory with experimental data. In this contribution, I … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
121
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(122 citation statements)
references
References 310 publications
1
121
0
Order By: Relevance
“…In calcium, earlier ab initio calculations have generally found that 62 Ca [58,59] is the heaviest bound isotope (see also Ref. [60]), with a very flat trend in binding energies beyond, leaving the location of the drip line ambiguous. The present analysis reflects that ambiguity; similar to oxygen the final bound nucleus could be closer to stability, but there is a reasonable probability that the drip line extends beyond 70 Ca, as predicted in the statistical analysis of Ref.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In calcium, earlier ab initio calculations have generally found that 62 Ca [58,59] is the heaviest bound isotope (see also Ref. [60]), with a very flat trend in binding energies beyond, leaving the location of the drip line ambiguous. The present analysis reflects that ambiguity; similar to oxygen the final bound nucleus could be closer to stability, but there is a reasonable probability that the drip line extends beyond 70 Ca, as predicted in the statistical analysis of Ref.…”
mentioning
confidence: 97%
“…Pinning down the neutron drip line to calcium and beyond is a flagship scientific motivation for next-generation rare-isotope beam facilities [3,4]. Indeed several neutron-rich isotopes, including 60 Ca, were recently discovered in this region [5]. Furthermore, knowledge of the neutron drip line is important for r-process simulations modeling the synthesis of heavy elements [6,7] that occurs in neutron-star mergers [8].…”
mentioning
confidence: 99%
“…Definition (7), however, is valid in a broader context where φ is a linear combination of several Salter determinants. A recent example [24] is the 11 Li nucleus described by a 9 Li+n+n structure, where the shellmodel description of 9 Li involves all Slater determinants (90) which can be built in the p shell. The oscillator parameter b is taken identical for the three clusters.…”
Section: Hamiltonian and Wave Functionsmentioning
confidence: 99%
“…a e-mail: pdesc@ulb.ac.be (corresponding author) Nuclear models are essentially divided in two categories: (1) in non-microscopic models, the internal structure of the clusters is neglected, and they interact by a nucleus-nucleus potential; (2) in microscopic models, the wave functions depend on the A nucleons of the system, and the Hamiltonian involves a nucleon-nucleon interaction. Recent developments in nuclear models [9][10][11] aim to find exact solutions of the A-body problem, but they present strong difficulties when the nucleon number increases. To simplify the problem, cluster models assume that the nucleons are grouped in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…In the present contribution, we have summarized the ideas for proceeding that emerged from presentations and discussions at the INT Crossroads, along with selective updates. This is not intended to be an exhaustive treatment but a summary of the main points from the INT program; for more extensive background, references, and updates, we refer the reader to recent reviews [10][11][12][13][14][15] and to the 2021 INT program "Nuclear Forces for Precision Nuclear Physics" https://sites.google.com/uw.edu/int/programs/21-1b.…”
mentioning
confidence: 99%